La gráfica de la cultura Manteño-Huancavilca en el diseño urbanístico de la Ciudad de Portoviejo - Andraus Quintero, Cesar (2023)
The Manteño-Huancavilca culture has not been studied in its entirety and has a graphic wealth of great contribution to graphic design. The objective of the work was to analyze the existing graphic identity in the objects found in Cerro Hojas y Jaboncillo for its application to t he urban design of the city of Portoviejo, from the regeneration of its historic center. For this, three fundamental fields were taken as reference: the identity of the Manteño-Huancavilca culture, the influence of pre-Columbian design in graphic design and the fundamentals of design. Once these fields were analyzed, they served as a reference for the understanding of the Manteño cultural codes according to their formal, structural and organizational coherence, based on the use of geometrically describable elements, which were capable of generating a configuration, by being repeated or formally related to conceive an autochthonous design, which can be used in isolation or in combination with foreign elements that guarantee the conservation of Manteño cultural elements in the portoviejo ́s identity.